EFEKTIVITAS METODE WAFA DALAM MENINGKATKAN HAFALAN PESERTA DIDIK PADA PEMBELAJARAN TAHFIDZ AL-QUR’AN KELAS VII DI SMP IT AR-RAHMAH MAKASSAR - Rahmadani H, Indah; Mustamin; Ahmad; Wahab, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Qur’an, as a guide for the lives of Muslims, teaches the importance of reading, understanding, and memorizing it. Early Qur’anic education serves as a foundation for shaping students’ character and spirituality. The Wafa Method, which emphasizes an audio-visual-kinesthetic approach, is believed to facilitate the memorization process. This study aims to determine the effectiveness of the Wafa Method in improving students’ memorization skills in the Qur’an memorization (tahfidz) learning of seventh-grade students at SMP IT Ar-Rahmah Makassar. Based on theoretical reviews, the Wafa Method has the potential to enhance students’ motivation, memorization quality, and mastery, thereby supporting optimal achievement in tahfidz learning.